The effectiveness of stress management training on mental health status of addicts referred to addiction treatment clinic - Romina Farhoudian (Chronic Diseases Journal, 2019)
BACKGROUND: Stress management is the ability of individuals to reduce stress and adapt to stressful situations. The objective in the present study was to investigate the effectiveness of stress management training on mental health of addicts quitting substance abuse referred to Raha addiction treatment clinic in Babol, Iran.